OM Forum—Innovative Online Platforms: Research Opportunities - Chen, Ying-Ju; Dai, Tinglong; Korpeoglu, C. Gizem; Körpeoğlu, Ersin; Sahin, Ozge; Tang, Christopher S.; Xiao, Shihong (Manufacturing and Service Operations Management, 2020)
Economic growth in many countries is increasingly driven by successful startups that operate as online platforms. These success stories have motivated us to define and classify various online platforms according to their business models. This study discusses strategic and operational issues arising from five types of online platforms (resource sharing, matching, crowdsourcing, review, and crowdfunding) and presents some research opportunities for operations management scholars to explore.